The Influence of Islamic Transformational Leadership on Psychology and Teachers' Work Ethic at Madrasah Tsanawiyah: Pengaruh Kepemimpinan Transformasional Islami terhadap Psikologi dan Etika Kerja Guru di Madrasah Tsanawiyah - siti maryam; Topan Iskandar (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2025)
This study aims to analyze the influence of Islamic transformational leadership on teacher discipline and work ethic at Madrasah Tsanawiyah Bagan Asahan. In the context of Islamic education, Islamic transformational leadership integrates modern leadership principles with Islamic values ​​based on trust, exemplary behavior, justice, and spiritual motivation. This study used a quantitative approach with a survey method of 30 teachers, and the data were analyzed using linear regression to test the influence between variables. The results showed that Islamic transformational leadership had a positive and significant effect on teacher discipline with a contribution of 39.9% and teacher work ethic by 46.4%. Simultaneously, Islamic transformational leadership contributed 55.5% to improving teacher discipline and work ethic. These findings indicate that the application of Islamic values ​​in leadership can simultaneously improve teacher discipline and work ethic. In conclusion, Islamic transformational leadership is effective in improving the quality of teacher discipline and work ethic in madrasahs, with important implications for the management of Islamic education based on spiritual and moral values.